2022
DOI: 10.1360/nso/20220037
|View full text |Cite
|
Sign up to set email alerts
|

Defect and interface control on graphitic carbon nitrides/upconversion nanocrystals for enhanced solar hydrogen production

Abstract: The effective utilization of solar energy for hydrogen production requires an abundant supply of thermodynamically active photo-electrons; however, the photocatalysts are generally impeded by insufficient light absorption and fast photocarrier recombination. Here, we report a multiple-regulated strategy to capture photons and boost photocarrier dynamics by developing a broadband photocatalyst composed of defect engineered g-C 3 N 4 (DCN) and upconversion NaYF 4 :Yb 3+ ,Tm 3+ (NYF) nanocrystals. Through a preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…An idea on using ammonia as an energy carrier to diminish CO 2 emissions is also proposed. Wang et al [1] reported a defect and interface engineering strategy to develop a broadband photocatalyst that enables to…”
mentioning
confidence: 99%
“…An idea on using ammonia as an energy carrier to diminish CO 2 emissions is also proposed. Wang et al [1] reported a defect and interface engineering strategy to develop a broadband photocatalyst that enables to…”
mentioning
confidence: 99%